Optimizing a Smart Green Office Platform to Enhance Students' Environmental Management Skills (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This vocational education initiative was motivated by the limited understanding among vocational school teachers and students regarding the concept of environmentally friendly offices, as well as the lack of digital learning media that support practical skill development in this area. The objective of the program was to develop and implement the Smart Green Office digital learning platform to enhance competencies in sustainable office management practices. Using a participatory action research and capacity-building approach, the initiative progressed through needs analysis, platform development, teacher training, implementation in classroom settings, and monitoring and evaluation. The results show that the platform successfully addressed the identified needs of partner schools. Teachers and students demonstrated a marked improvement in their understanding of Green Office principles and in their ability to utilize digital tools for office management. Pre- and post-test evaluations revealed significant gains in both cognitive and practical learning outcomes, including increased environmental awareness and more sustainable behaviors in daily school activities. The platform was also found to be user-friendly, aligned with the vocational curriculum, and adaptable for broader application in similar educational contexts. This initiative provides a contextual and scalable learning solution that supports both environmental literacy and digital competence in vocational education.